Cuidado de enfermería en recién nacidos hospitalizados - Reyes Alfaro, Cecilia Elizabeth (2015)
Nursing work aimed to describe nursing care in newborns hospitalized and reflect on their learning and work, so it make a theoretical and practical proposal for custodial care of newborns. The theoretical support constitute the theoretical perspectives of humane care Boff (1999) and Waldow (1998). The study is qualitative, exploratory and descriptive, which allowed capture the object of study from the daily work of nurses. Data collection was made through semi-structured interviews and participant observation, the sample were eight nurses who cared for the newborn and determined by information overload. From discourse analysis results are organized into two categories: 1) The care of the sick body in the manifestation of his ailment, from the perspective of body-object that needs attention in their physiological needs. 2) The / the nurse / or in situations of care and not care, with subcategories: a) Resonances of care, evidenced by affection, love and therapeutic touch. b) Disonancias care, indicative; lack of support, lack of time, discomfort. The results show strengths and weaknesses of nurses in newborn care, the need to integrate knowledge to bring the practice of holistic care and prevent technical care devalue humanized care is identified; It is necessary to broaden opportunities for continuous training and reflection on knowledge and nursing practice, deepen knowledge of the theoretical basis of compassionate care that support the rationale of the profession and find balance between theoretical care and humanized care.